2014
DOI: 10.1002/cbic.201300805
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of E. coli LptC: Interaction with LPS and a Synthetic Ligand

Abstract: Lipopolysaccharide (LPS), the main cell-surface molecular constituent of Gram-negative bacteria, is synthesized in the inner membrane (IM) and transported to the outer membrane (OM) by the Lpt (lipopolysaccharide transport) machinery. Neosynthesized LPS is first flipped by MsbA across the IM, then transported to the OM by seven Lpt proteins located in the IM (LptBCFG), in the periplasm (LptA), and in the OM (LptDE). A functional OM is essential to bacterial viability and requires correct placement of LPS in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…In vitro studies on the soluble domain of LptC (amino acids 24–191) show that LPS co‐elutes with 6xHis‐tagged LptC from affinity resin and suggest that the transfer of LPS from LptC to LptA is unidirectional . In addition, a dissociation constant was determined for LptC:LOS (lipo‐oligosaccharide, LPS lacking the O‐antigen) . In vivo studies on 23 mutants of LptC substituted with the unnatural amino acid p PBA indicated that LPS could cross‐link with four of the sites tested, the N‐terminal site T47 p PBA and interior‐facing sites F78 p PBA, A172 p PBA, and Y182 p PBA upon irradiation with UV light, supporting the hypothesis that LPS binds to the interior fold of LptC .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies on the soluble domain of LptC (amino acids 24–191) show that LPS co‐elutes with 6xHis‐tagged LptC from affinity resin and suggest that the transfer of LPS from LptC to LptA is unidirectional . In addition, a dissociation constant was determined for LptC:LOS (lipo‐oligosaccharide, LPS lacking the O‐antigen) . In vivo studies on 23 mutants of LptC substituted with the unnatural amino acid p PBA indicated that LPS could cross‐link with four of the sites tested, the N‐terminal site T47 p PBA and interior‐facing sites F78 p PBA, A172 p PBA, and Y182 p PBA upon irradiation with UV light, supporting the hypothesis that LPS binds to the interior fold of LptC .…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro LPS binding assay was based on a previous protocol with a few modifications (Sestito et al 2014). Briefly, purified ArnT protein (200 µg) was incubated in 0.5 mL of Phosphate/NaCl buffer (50 mM phosphate buffer, pH 8.0, 150 mM NaCl) with 0.06 mL of HisLink protein purification resin (Promega) for 90 min on a rotary shaker at 4°C.…”
Section: Lps Binding By Resin-capture Methodsmentioning
confidence: 99%
“…This region in the predicted ArnT model is the only one that has a pocket of a diameter such that could accommodate the lipid A molecule. To explore this hypothesis, we performed an in vitro binding assay using purified ArnT proteins and a resin-capture procedure previously described (Sestito et al 2014). ArnT was immobilized on the Ni 2+ -NTA resin and then Alexa-conjugated LPS from S. enterica Serovar Minnesota was added.…”
Section: The C-terminal Domain Of Arnt Is Required For Lps Bindingmentioning
confidence: 99%
“…Based on Lpt architecture and function, either the assembly of the machinery or the binding of individual proteins to LPS can be targeted and inhibited. Inhibitors of the LptB ATPase and of the LptC IM bitopic proteins have been identified. Still, none of these compounds is able to kill bacteria possessing an intact OM, highlighting once more the importance of the OM barrier properties for bacterial survival.…”
Section: Targeting Lps Biogenesis Pathway For the Discovery Of Novel mentioning
confidence: 99%